The changing role of government in New Zealand: implications for the training and development of public servants - Tanner, Ross M. (1998)
This article addresses the reform of public management in New Zealand with reference to the changing role of government and its implications for public service training and development. The reform initiatives taken in New Zealand, and the lessons drawn from them, have been of considerable interest to many other countries which now have similar programmes of reform underway. At the outset of the reform programme, government interventions and controls were more pervasive and rigid than in any other developed economy. The government provided a very wide range of goods and services to its citizens, including an extensive system of social service delivery. It also directly managed a large portion of the economy through its ownership of enterprises in many sectors. The role of the state was broadly defined and government departments tended to be large and have a sectoral rather than a functional design
Keywords: Training - New Zealand; Civil service - New Zealand; Civil service